Penerapan Model Problem Based Learning Berbantuan Media Lumio dalam Peningkatan Aktivitas dan Hasil Belajar Siswa Kelas V SD Negeri 6 Ampenan - Masita; Suryani, Nur Rahmah; Musaddat, Syaiful (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2025)
This research was motivated by the lack of active student participation in class and the low learning outcomes of fifth-grade students at SDN 6 Ampenan in Science subjects. Based on the mid-semester exam data of 34 students, only 29.4% (10 students) achieved the minimum mastery criterion (KKM), while the remaining 70.5% (24 students) scored below the required KKM of 75. This issue was caused by limited school facilities and the use of learning models and media that were not yet suitable for the material being taught. In addition, students’ participation during lessons remained low, both in asking and answering questions. To address these problems, the researcher implemented an improvement effort using the Problem-Based Learning (PBL) model assisted by Lumio media. The purpose of this study was to improve student activity and Science learning outcomes by applying the Problem-Based Learning model assisted by Lumio media for fifth-grade students at SDN 6 Ampenan. This research employed Classroom Action Research (CAR) conducted in two cycles. Each cycle consisted of four stages: planning, implementation, observation and evaluation, and reflection. The subjects of this study were 34 fifth-grade students of SDN 6 Ampenan, consisting of 15 male and 19 female students. Data were collected through written tests administered at the end of each cycle, while teacher and student activities were assessed through observation sheets. The research results showed an increase in student activity and learning outcomes. In the first cycle, student activeness reached 75%, which increased to 93.75% in the second cycle. Furthermore, students’ average learning scores improved from 80.31 in the first cycle (with a mastery rate of 68.75%) to 86.47 in the second cycle (with a classical mastery rate of 88.23%). Therefore, it can be concluded that the implementation of the Problem-Based Learning model assisted by Lumio media, when carried out optimally, can enhance both student activity and Science learning outcomes among fifth-grade students at SDN 6 Ampenan.